Influence of Procurement Quality Management on Performance of Manufacturing Firms in Kenya - Mutungi , Jacinta Kalondu; Ndeto, Charles (International Journal of Supply Chain and Logistics, 2023)
Purpose: The overall objective of this study was to examine the influence of procurement quality management on performance of manufacturing firms in Kenya, with an aim of making recommendations on proper use of procurement quality management in the manufacturing sector. The study aimed to establish how process management, continuous improvement, supplier management and customer focus influence performance of manufacturing firms Methodology: This research study adopted a descriptive research design. The researcher preferred this method because it allowed an in-depth study of the subject. To gather data, structured questionnaire was used to collect data. The study population was the manufacturing firms in Nairobi; the respondents were the designated heads of procurement of these firms. 200 heads of procurement were selected using stratified random sampling. Once collected, data was analyzed using descriptive and inferential statistics.Quantitative data was analyzed using multiple regression analysis. The qualitative data generated was analyzed by use of Statistical Package of Social Sciences (SPSS) version 24. Results and conclusion: The response rate of the study was 86%. The findings of the study indicated that process management, continuous improvement, supplier management and customer focus have a positive relationship with performance in manufacturing firms. The regression results revealed that procurement quality management practices identified in the study, that is, process management, continuous improvement, supplier management and customer focus combined could explain approximately 66.3% of the variations in the performance of manufacturing firms. The other 33.7% may be attributed to other strategies not explained by the model or the variables. Unique Contribution to Theory, Policy and Practice: The study recommended that manufacturing firms should embrace procurement total quality practices so as to improve their performance and further researches should to be carried out in other institutions to find out if the same results can be obtained.